Former male elite athletes sustain fewer fragility fractures than expected - Tveit, M.; Rosengren, B. E.; Nilsson, J.; Karlsson, M. K. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Background: Physical activity during growth and adolescence is associated with high peak bone mass, and may as a result prevent osteoporosis later in life. It is therefore possible that physical activity during youth could serve as a strategy to reduce the risk of fragility fractures at advanced ages. However, it is yet currently unclear whether former athletes actually have fewer fractures than expected with age. Purpose: This study aimed to evaluate fracture incidence in former male athletes. Methods: In a retrospective matched controlled design lifetime incidence of fractures was registered through a mailed questionnaire sent to 709 former male athletes now with a median age of 70 years (range 50-93), who had given up regular sports activity a median 35 years (range 1-63) ago, and to 1368 male controls aged a median 70 years (range 51-93). Fragility fractures were defined as factures due to a light trauma and after age 50 in proximal humerus, distal radius, vertebra, pelvis, hip, and tibial condyles. Both cohorts were normally distributed (Shapiro Wilk`s test). Data are presented as means with 95% confidence intervals (95% CI). Group differences were evaluated by Student`s t-test between means and chi-square test. Differences between athletes and controls in time to first fracture were evaluated by Kaplan-Meier survival curves, and rate ratios (RR) were estimated by Poison distribution. Results: The anthropometrics and lifestyle factors were most similar between the groups. There was no group difference in current Body Mass Index and level of leisure-time physical activity. After retirement from sports (age 35 years), the former athletes had a lower risk of sustaining any fractures with a RR of 0.70 (0.52, 0.93), a lower risk of sustaining any fragility fractures (RR 0.50 (0.27, 0.89)), and a lower risk of sustaining a distal radius fracture (RR 0.29 (0.09, 0.74)), but did not reach statistical significance as regard to hip fracture after age 50 (RR 0.79 (0.28, 2.00)) (Figure 1). Conclusions: Intense physical activity during growth and young adulthood is in retired sportsmen associated with a lower risk of sustaining a fracture than expected by age. In a wider perspective, this indicates that physical activity in younger years could be recommended as a feasible strategy to reduce the incidence of fragility fractures in older ages.